Application development of ammonia gas leakage detection and monitoring system - Muhammad Syazwan, Bunander (2022)
The purpose of this project is to improve irrelevant measurement methods held or mounted on walls that limit the purpose of measuring only. The project integrates Internet-of-Things technology that helps monitor sensor readings from a safe distance, locate areas where ammonia gas is leaking based on readings from pressure sensors and also includes a prevention system that serves as feedback that responds to sensor readings that will control water pumps, fans, and solenoid valves to control ammonia gas leakage. It is also equipped with a GPS system where it will provide the location of areas that have gas leakage. The project system revolves around the transmission of data from the sensing unit to the broker where it is stored momentarily for the Blynk app while for the web ThingSpeak, the data can be stored for a long time and can be exported. The data is displayed onto mobile web and application where users can access to monitor readings from the sensors. Data transmission is done through the NodeMCU to read data from inputs and outputs and send it to Blynk applications and the ThingSpeak protocol web. The results obtained during the prototype testing showed a functioning Blynk and ThingSpeak web application where the meter showed readings correctly according to its function, as well as the GPS system, provides accurate latitude and longitude. This project of ammonia gas leakage detection and monitoring system has been successfully developed and functionally. There is some recommendation for this project which is by changing the gas sensor to MQ137 because the MQ-135 is an air quality sensor not totally ammonia gas sensor and change to others platform for web application monitoring which has low delay in transfer data.